Logical Implication
- I1: Simplification
- P∧Q ⇒ P
- P∧Q ⇒ Q
- I2:
- P ⇒ P∨Q
- Q ⇒ P∨Q
- I3
- ¬P ⇒ P→Q
- Q ⇒ P→Q
- I4
- ¬(P→Q) ⇒ P
- ¬(P→Q) ⇒ ¬Q
- I5
- ¬P∧(P∨Q) ⇒ Q
- I6:
- P∧(P→Q) ⇒ Q
- ¬Q∧(P→Q) ⇒ ¬P
- I7
- (P→Q)∧(Q→R) ⇒ P→R
- I8
- (P∨Q)∧(P→R)∧(Q→R) ⇒ R
- I9
- (∀x:A(x))∨(∀x:B(x)) ⇒ ∀x:(A(x)∨B(x))
- ∃x:(A(x)∧B(x)) ⇒ (∃x:A(x))∧(∃x:B(x))
Logical Equivalence
- E1: Idempotence
- P∨P ⇔ P
- P∧P ⇔ P
- E2: Double negative elimination
- ¬¬P ⇔ P
- E3: Commutativity
- P∧Q ⇔ Q∧P
- P∨Q ⇔ Q∨P
- E4: Associativity
- (P∧Q)∧R ⇔ P∧(Q∧R)
- (P∨Q)∨R ⇔ P∨(Q∨R)
- E5: Distributivity
- P∧(Q∨R) ⇔ (P∧R)∨(Q∧R)
- P∨(Q∧R) ⇔ (P∨R)∧(Q∨R)
- E6: Reflexivity
- P∧T ⇔ P
- P∨F ⇔ P
- E7:
- P∧F ⇔ F
- P∨T ⇔ T
- E8:
- P∧¬P ⇔ F
- P∨¬P ⇔ T
- E9: De Morgan’s law
- ¬(P∧Q) ⇔ ¬P∨¬Q
- ¬(P∨Q) ⇔ ¬P∧¬Q
- E10:
- P∨(P∧Q) ⇔ P
- P∧(P∨Q) ⇔ P
- E11
- P→Q ⇔ ¬P∨Q
- ¬(P→Q) ⇔ P∧¬Q
- E12
- P→Q ⇔ ¬Q→¬P
- E13
- P→(Q→R) ⇔ (P∧Q)→R
- E14
- (P→Q)∧(P→R) ⇔ P→(Q∧R)
- E15
- ¬(P⇌Q) ⇔ P⇌¬Q
- E16
- P⇌Q ⇔ (P→Q)∧(Q→P)
- P⇌Q ⇔ (P∧Q)∨(¬P∧¬Q)
- E17:
- ∃x:(A(x)∨B(x)) ⇔ (∃x:A(x))∨(∃x:B(x))
- ∀x:(A(x)∧B(x)) ⇔ (∀x:A(x))∧(∀x:B(x))
- E18:
- ¬∃x:A(x) ⇔ ∀x:¬A(x)
- ¬∀x:A(x) ⇔ ∃x:¬A(x)
- E19:
- ∀x:(A∧B(x)) ⇔ A∧(∀x:B(x))
- ∀x:(A∨B(x)) ⇔ A∨(∀x:B(x))
- ∃x:(A∧B(x)) ⇔ A∧(∃x:B(x))
- ∃x:(A∨B(x)) ⇔ A∨(∃x:B(x))
- E20
- (∀x:A(x))→B ⇔ ∃x:(A(x)→B)
- (∃x:A(x))→B ⇔ ∀x:(A(x)→B)
- A→(∀x:B(x)) ⇔ ∀x:(A→B(x))
- A→(∃x:B(x)) ⇔ ∃x:(A→B(x))
- II1
- ∀x∀y:P(x,y) ⇒ ∀y∃x:P(x,y)
- ∀x∀y:P(x,y) ⇒ ∃y∀x:P(x,y)
- II2
- ∃x∀y:P(x,y) ⇒ ∀y∃x:P(x,y)
- II3
- ∀x∃y:P(x,y) ⇒ ∃y∃x:P(x,y)
- EE1
- ∀x∀y:P(x,y) ⇔ ∀y∀x:P(x,y)
- ∃x∃y:P(x,y) ⇔ ∃y∃x:P(x,y)